The Zulu ceramic tradition in Msinga, South Africa - Fowler, K. D. (Southern African Humanities, 2011)
This paper summarizes fieldwork conducted in 2009 with Zulu potters in the Msinga region of KwaZulu-Natal, South Africa. New data collected from this area of the Upper Thukela Basin are used to compare and contrast production technology, the scale of production, distribution, seasonality, and labour organization with Zulu potters in the Lower Basin. The results of this study indicate that pottery production in Msinga has a distinctive character, which generates an equally distinctive ceramic style. This report demonstrates that potters’ social networks influence the visible and technical dimensions of pottery in the Thukela Basin. A better understanding of these social influences provides explanations for pottery variability that link the social context of ceramic production with style.